Halal Certification, Halal Awareness, and Product Quality: A Three-Way Interaction and its Influence on Purchase Intention for MSME Products - Alfiansyah, Rifky (IJBLE Scientific Publications Community Inc., 2024)
This study seeks to explore how Halal Certification, Halal Awareness, and Product Quality impact the purchase intentions of MSMEs in Cirebon, utilizing quantitative methodologies. The data were meticulously analyzed using statistical procedures and purposive sampling. The study utilized SmartPLS 3 software to assess the theoretical framework. The investigation's outcomes reveal that Halal Certification and Halal Awareness exert a substantial and positive influence on Purchase Intention. Construct validity was verified, incorporating assessments of both convergent and discriminant validity, while construct reliability was evaluated by conducting tests for internal consistency. Bootstrapping methods were employed to execute significance assessment. Concurrently, it was observed that Product Quality notably boosts Purchase Intention. For stakeholders and academics associated with MSMEs, these results provide essential understanding into how Purchase Intention can be understood and improved by examining the impacts of Halal Certification, Halal Awareness, and Product Quality.